2016
DOI: 10.4103/1817-1737.191866
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, airflow obstruction and dyspnea and body mass index, airflow obstruction, dyspnea scores, age and pack years-predictive properties of new multidimensional prognostic indices of chronic obstructive pulmonary disease in primary care

Abstract: BACKGROUND:The assessment of the severity of chronic obstructive pulmonary disease (COPD) should involve a multidimensional approach that is now clearly shown to be better than using spirometric impairment alone. The aim of this study is to validate and compare novel tools without an exercise test and to extend prognostic value to patients with less severe impairment of Forced expiratory volume 1 s.METHODS:A prospective, observational, primary care cohort study identified 458 eligible patients recruited from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Supplementary table F shows all the external validation studies of the prognostic models for outcome prediction in COPD patients 2325 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary table F shows all the external validation studies of the prognostic models for outcome prediction in COPD patients 2325 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81…”
Section: Resultsmentioning
confidence: 99%
“…24 Low muscle mass and increased adiposity were generally associated with increased airway obstruction, lower 6MWD, increased dyspnea severity, and low or increased BMI, respectively. The BODE index is multifactorial and observed to be associated with biomarkers of inflammation (TNF-alpha and leptin levels), 49 physical inactivity, 50 malnutrition, hypoxemia, and smoking, 51 known risk factors for disease progression. Furthermore, BODE index has been shown to be responsive to pulmonary rehabilitation with greater than 70% of 83 COPD participants demonstrating > 1 point BODE index change, specifically in the indices of lung function, dyspnea, and exercise capacity, but no change in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Mean BODE index in our study was 4.03. Fanny et al (7) conducted a prospective cohort study involving 243(208males) COPD patients hospitalized for acute exacerbations of COPD [AECOPD], in this study distribution of BODE index is as shown in figure 5. In our study group, 66.7% patients belonged to quartile 2 and 3, in comparison to above study population, in which 61% patients belonged to quartile 2 and 3.…”
Section: Discussionmentioning
confidence: 99%